PENANGANAN GURU PAUD TERHADAP KECEMASAN BERPISAH PADA ANAK DI SEKOLAH - Ambari, Prinda Kartika Mayang; Panjaitan, Lena Nesyana; Kartika, Aniva (Universitas Muhammadiyah Jember, 2020)
Separation anxiety can occur to anyone, including children. Children who are in a new situation or environment that makes them separate from sticking figures can experience separation anxiety. Factors that cause separation anxiety according to Moldovan & Moldovan (2013) are genetic and environmental. Separation anxiety is often reported to occur at school. This requires treatment as soon as possible so as not to develop into a disorder. This research was conducted to see how the picture of children experiencing anxiety separated at school and the handling done by the teacher at school. Subjects in the study were 4 teachers who teach in PAUD. Data collection methods through interviews, observations, and separation questionnaires anxiety. The technique used by researchers in selecting study participants is the purposive sampling method. The results of the study show that the treatment has not shown maximum results. n the separation experienced by children in schools on average is still high.